IMPLEMENTASI MANAJEMEN DAN KEPEMIMPINAN PENDIDIKAN DI SMP NEGERI 1 BEJEN KABUPATEN TEMANGGUNG - Lestari, Eny; Oktarina, Nina; Rokhman, Fathur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the implementation of management and leadership at SMP Negeri 1 Bejen, Temanggung Regency. Even though this school is located in a hilly area and far from the hustle and bustle of the city, it has managed to show good achievements. This success cannot be separated from the management and leadership role of the school principal. This study uses a qualitative approach with a case study method, and involves the participation of school principals, as well as teaching and education staff. Data collection was carried out by means of observation, surveys and document analysis. The research results show that the principal of SMP Negeri 1 Bejen 1applies various leadership styles, namely democratic, supportive and autocratic, according to the situation and needs. The school principal also applies a situational approach in various contexts, namely directive, coaching, supporting, and delegating. The implementation of management and leadership at SMP Negeri 1 Bejen has proven to be effective and achieves school goals, improves the quality of learning, and improves the welfare of the school community. It is hoped that this research can contribute to the development of leadership theory and practice and educational management. However, communication with external stakeholders needs to be improved to expand collaboration and support school program development. The conclusion of this research shows that flexible and adaptive principal leadership plays an important role in achieving the goals of quality education at SMP Negeri 1 Bejen